Utilization of ChatGPT by Communication Science Students at Teuku Umar University in Completing Final Assignments - Imam Dwi Ananda; Al Zuhri (Sekolah Tinggi Ilmu Tarbiyah Insan Kamil Bogor, 2025)
This research is motivated by the low utilization of ChatGPT among students of the Communication Science Study Program at Teuku Umar University in assisting them to complete their final assignments. In fact, ChatGPT can help simplify the process of writing final assignments for students. This study employs a descriptive qualitative method by describing findings related to the research topic in the form of sentences. Purposive sampling was used as the technique for selecting informants, resulting in three informants who met the criteria. The theory applied in this research is Everett Rogers' Diffusion of Innovations.The findings reveal that all three informants agreed that ChatGPT is a new, sophisticated, and fast innovation. However, their utilization of ChatGPT was limited to seeking recommendations for writing research backgrounds, theoretical frameworks, and enriching academic vocabulary. Additionally, two of the three informants learned about ChatGPT through Instagram as a communication channel, while the third informant discovered it through a friend. The adoption period of ChatGPT varied among the informants: the first informant adopted it coinciding with its release in 2022, while the other two adopted it a year later, in 2023. This indicates that some informants were early adopters, while others were late adopters. Furthermore, all three informants emphasized that Teuku Umar University, as a social system, needs to establish regulations regarding the use of ChatGPT for students. These regulations would provide clear guidelines, prevent misuse, and address potential confusion and uncertainty.